AHRC Efforts Action to Reduce Racial Discrimination Cases Occur in Australia - Adelaide, Alyne; Corymbia, Bindi; Chloe, Ambelin (PT. Riset Press International, 2023)
This article discusses the efforts of the Australian Human Rights Commission (AHRC) to reduce cases of racial discrimination in Australia 2015-2018. The AHRC's efforts are defined in five rules and procedures for resolving complaints of racial discrimination. Among them are socialization or early warning, complaints and investigations, compliance, continuation of legal action, and public hearings. The moment Australia ratified the United Nations Human Rights Commission (UNHRC) rules, namely the CERD rules on the International Convention on the Elimination of All Forms of Racial Discrimination which sparked the 1975 Racial Discrimination Act that could form the formation of the AHRC in 1986. In principle UNHRC is an organization known as the regime adopted in Australia in the form of the AHRC. This journal aims to discuss, describe, and find out the efforts of the Australian Commission on Human Rights in reducing cases of racial discrimination in Australia 2015-2018. Describes the rules and procedures for resolving racial discrimination complaints received by the AHRC through the five stages of resolution. After that it analyzes whether the five rules and procedures applied by the AHRC are implemented optimally to reduce cases of racial discrimination that occurred in Australia in 2015-2018.